Laminated and functionally graded HAP/YSZ composites prepared using powder processing - Muhammad Nurhaikal Azhar Mohd Aziz (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Hydroxyapatite (HAP) ceramics have been widely studie to improve strength and toughness the from of composites and coating. New microstructual designs and processing methodologies are strill needed for the improvement of the mechanical properties of HAP-based caramics.This study was to prepare lamianted and functionally graded HAP/yttria-stabilized zirconia. (YSZ) composite by using conventionall sintering.